Integrating Technology and Heritage Design for Climate Resilient Courtyard House in Arid Region - Afaq H. Chohan; Jihad Awad; Muhammad A. Ismail; Mohammad S. Arar (Salehan Institute of Higher Education, 2024)
This research has investigated the sustainability and climate resilience of courtyard houses of adobe architecture in the UAE. It analyzed design effectiveness in terms of power consumption, CO2 emissions, thermal comfort, and daylight use, employing simulations to assess building structures and construction systems. Adopting a three-phase mixed-methods approach, the study began with a literature review on courtyard house design, construction, and environmental performance, emphasizing sustainable design and passive ventilation. The second phase involved a case study of a UAE courtyard house (Al Midfa), including site visits, interviews, and energy consumption and CO2 emission data collection. The final phase used building energy simulation software to model energy performance and evaluate passive ventilation's role in reducing energy consumption and CO2 emissions, with simulation results validated against real-world data. Advanced Sefaira simulations with the Energy Plus Engine identified one out of seven modified models (M5) as exceptionally thermally efficient, influencing the architectural design of the Al Midfa house. To transform the Al Midfa house into a sustainable climate-resistant structure, the research suggested retrofitting with new glazing and insulation on the inside of external walls and on the roof surface at a combined U-value of 0.4 W/m2to enhance energy efficiency without altering the exterior. A notable innovation was the use of injected cellulose insulation in wall systems, combining efficient insulation with architectural aesthetics, signifying a shift towards energy-efficient interior modifications. The study's findings contribute to the evolution of traditional house designs toward climate change resilience and a sustainable future. Doi: 10.28991/CEJ-2024-010-03-018 Full Text: PDF